Effectiveness Education of Cadres Stunting to Behavior Toddler Mothers Overcome Stunting in Deli Serdang North Sumatera and Aceh Besar, Banda Aceh, Indonesia - Samsider Sitorus; Zuraidah Nasution; Ngena Ria; Rachmawati (Postgraduate, University of Mataram, 2023)
Introduction stunting was a failure to achieve optimal growth caused by condition of malnutrition in a long time. Toddlers grow short and low child intelligence levels result in a burden on the dating time. Due to the limited working capacity, reduction of body activity and complication of content in women because it has a small pelvic size and the risk of giving birth to infants with low birth weight. Know effectiveness of education by stunting cadres on the behavior of toddler mothers prevents stunting, and analyzing factors of stunting event in infants under the five years Methods experimental quasi design. Research respondents are toddler mothers with toddlers of 80. bivariate, with different tests (t–test). multivariate, with multiple logistics regression. Result the average difference in the behavior of the toddler mothers before and after education was 0.55. This increase in the average behavior of p≤ 0.001 < α (0.05). The most influential factor in the nutritional status of toddlers (stunting) with the value B = 3.562 and p≤ 0.001. Conclusion Education able to improve behavior mothers toddlers to prevent stunting. The most influential factor in the stunting event mothers toddlers was the education